Pindborg tumor: Pathology with special stains - Swati Shrikant Gotmare; Treville Pereira; Subraj Shetty; Kashmira S Kesarkar (Wolters Kluwer Medknow Publications, 2018)
Odontogenic tumors constitute a wide spectrum of lesions ranging from malignant and benign neoplasms to dental hamartomas, all derived from the epithelial and ectomesenchymal remnants of the tooth forming apparatus. Calcifying epithelial odontogenic tumor (CEOT) is an uncommon, benign epithelial odontogenic tumor first described by Pindborg in 1956. It is a universally accepted eponym for this neoplasm. Pindborg tumor or CEOT is a locally aggressive neoplasm that accounts for 1% of the total odontogenic tumors, with recurrence in 14% of cases. The etiology of this tumor remains an enigma to the clinician. Pindborg suggested that the tumor arises from the remnants of reduced enamel epithelium of an unerupted tooth. Recent studies in literature report that the tumor arises from stratum intermedium. We report a case of Pindborg tumor in a 22-year-old male patient in the left mandibular posterior region. Radiographically, a well-defined radiolucency was associated with unerupted mandibular second molar which was displaced to the inferior border of the mandible. Along with routine haematoxylin and eosin stains, this case reports histopathological findings using Congo red stain and modified Gallegos stain.